Interaction Impedance from the Equivalent Circuit Parameters of a Dielectric-Loaded Helical Slow-Wave Structure of a Traveling-Wave Tube - Singh V.P.; Murty K.V.R.; Basu B.N. (My University, 2025)
The interaction impedance of the dielectic-loaded helical slow-wave structure of a traveling-wave tube, with or without a metal envelope, has been found by integrating the Poynting vector across the structure cross section. A simple empirical relation is then suggested to predict the value of the interaction impedance from the knowledge of the equivalent circuit parameters of the structure without requiring the complex integration of the Poynting vector. © 1988 IEEE